2007
DOI: 10.1016/j.molcel.2007.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of p53 Function by SET8-Mediated Methylation at Lysine 382

Abstract: Reversible covalent methylation of lysine residues on histone proteins constitutes a principal molecular mechanism that links chromatin states to diverse biological outcomes. Recently, lysine methylation has been observed on nonhistone proteins, suggesting broad cellular roles for the enzymes generating and removing methyl moieties. Here we report that the lysine methyltransferase enzyme SET8/PR-Set7 regulates the tumor suppressor protein p53. We find that SET8 specifically monomethylates p53 at lysine 382 (p5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
434
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 395 publications
(446 citation statements)
references
References 39 publications
(55 reference statements)
11
434
0
1
Order By: Relevance
“…In contrast, we demonstrated that the absence of PR-Set7 and its enzymatic function in human cells results in the activation of ATM and an associated significant increase in damaged DNA. Because PR-Set7 was recently shown to also methylate p53 and regulate its function (47), it was highly likely that the observed cell cycle arrest and activation of DNA damage pathways in the absence of PR-Set7 was due to altered p53 function. However, in the paired wild type and p53 Ϫ/Ϫ HCT116 cells lacking PR-Set7 enzymatic function, we observed the identical cell cycle defects and DNA damage regardless of p53 status, indicating that p53 methylation by PR-Set7 is not responsible for these phenotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, we demonstrated that the absence of PR-Set7 and its enzymatic function in human cells results in the activation of ATM and an associated significant increase in damaged DNA. Because PR-Set7 was recently shown to also methylate p53 and regulate its function (47), it was highly likely that the observed cell cycle arrest and activation of DNA damage pathways in the absence of PR-Set7 was due to altered p53 function. However, in the paired wild type and p53 Ϫ/Ϫ HCT116 cells lacking PR-Set7 enzymatic function, we observed the identical cell cycle defects and DNA damage regardless of p53 status, indicating that p53 methylation by PR-Set7 is not responsible for these phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Occur Independently of p53-It was recently reported that PRSet7 can monomethylate p53 in vivo and negatively regulate its function (47). The report showed that the lack of PR-Set7 enhanced the proapoptotic and cell cycle checkpoint functions of p53.…”
Section: Aberrant Phenotypes Associated With the Absence Of Pr-set7mentioning
confidence: 98%
“…The siRNA sequences used were: TP53 (5 0 -GAAAUUUGCGUGUGGAGUAUU-3 0 ; ref. 21), CDKN1A (5 0 -CAGGCGGUUAUGAAAUUCA-3 0 ), and Luciferase (GL2; 5 0 -CGUACGCGGAAUACUUCGA-3 0 ). Reagents were purchased from the following suppliers: camptothecin, nocodazole, and MG132 were from Sigma, and FdUrd, FTD, and oxaliplatin were from Tokyo Chemical Industry.…”
Section: Cell Culture and Reagentsmentioning
confidence: 99%
“…Although histones are major substrates for histonemodifying enzymes such as HATs and HMTs, it is widely known that histone-modifying enzymes have nonhistone substrates, such as p53 (Shi et al 2007). In contrast, ATPdependent chromatin remodeling complexes have only been shown to remodel nucleosomes through their ability to disrupt DNA-histone interactions.…”
Section: Nonchromatin Substrates For Atp-dependent Chromatin Remodelimentioning
confidence: 99%